Pelatihan aplikasi screen recorder dan video conference guna meningkatkan proses belajar mengajar - Triana Elizabeth; Dicky Pratama; Derry Alamsyah; Yoannita Yoannita; Inayatullah Inayatullah; Tinaliah Tinaliah (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
At the beginning of 2020, Indonesia faced the Covid-19 virus pandemic. As a result, changes occurred in all sectors, including the education sector. The change in the learning model from offline to online makes it difficult for Indonesian because they are not accustomed to using digital technology in the learning process. Therefore, this service activity aims to train 10 Dewi Sartika Palembang Kindergarten teachers using video conferencing applications (Google Meet) and screen recorders (AZ Screen Recorder) to support a more optimal learning process. This activity is carried out by implementing health protocols. Based on the results of the evaluation of the training activities, it was obtained that all teachers were able to use the Google Meet and AZ Screen Recorder applications and were able to make learning videos and use them in the learning process. However, many students cannot participate in the online learning process because of poor internet signals. This problem can be overcome by sending a video recording of the learning process.